2022
DOI: 10.1111/jipb.13241
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid synthesis inhibitor fumonisin B1 causes verticillium wilt in cotton

Abstract: Verticillium wilt caused by Verticillium dahliae is a major disease of cotton. Acidic proteinlipopolysaccharide complexes are thought to be the toxins responsible for its symptoms. Here, we determined that the sphingolipid biosynthesis inhibitor fumonisin B1 (FB1) acts as a toxin and phenocopies the symptoms induced by V. dahliae. Knocking out genes required for FB1 biosynthesis reduced V. dahliae pathogenicity. Moreover, we showed that overexpression of a FB1 and V. dahliae both downregulated gene, GhIQD10, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…HPLC assay showed that the peak profile of the Δ VdDrs2 fermentation broth was different with the wild type: both the peaks height and peaks area of the Δ VdDrs2 fermentation broth were lower than those of the wild type, showing that a decrease in metabolites secreted by knockout strain ( Figures 6A,B ). As there are two toxins, SFA and FB1, identified in V. dahliae ( Zhang et al, 2016 ; Xu et al, 2022 ), we quantified the amount of these two toxins, in the fermentation broths of Vd991 and Δ VdDrs2 . The amounts of these two VW toxins produced by one mg of Δ VdDrs2 mycelia were significantly lower than that by wild type ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…HPLC assay showed that the peak profile of the Δ VdDrs2 fermentation broth was different with the wild type: both the peaks height and peaks area of the Δ VdDrs2 fermentation broth were lower than those of the wild type, showing that a decrease in metabolites secreted by knockout strain ( Figures 6A,B ). As there are two toxins, SFA and FB1, identified in V. dahliae ( Zhang et al, 2016 ; Xu et al, 2022 ), we quantified the amount of these two toxins, in the fermentation broths of Vd991 and Δ VdDrs2 . The amounts of these two VW toxins produced by one mg of Δ VdDrs2 mycelia were significantly lower than that by wild type ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…Sphingolipids were extracted from the ten seeds after 0 h, 6 h, 12 h, and 24 h imbibition with three biological repeats and detected by LipidALL Technologies Co. Ltd. (http://www.lipidall.com/) as described by Xu et al [51]. Brie y, collected soybean seeds were weighed and inactivated with hot isopropanol using a modi ed protocol as described [52].…”
Section: Extraction and Detection Of Sphingolipidsmentioning
confidence: 99%
“…For F. proliferatum , which causes rice spikelet rot disease, it was shown that the disruption of several genes leading to loss of fumonisin production caused reduced virulence [ 23 ]. Also, in Verticillium dahliae causing wilting disease in cotton, fumonisin-deficient knockout strains were less virulent [ 24 ]. In the case of Alternaria alternata f.sp.…”
Section: Introductionmentioning
confidence: 99%